Lymphoplasmacyte rich meningioma: a rare variant of meningioma mimicking diffuse granulomatous disease with leptomeningeal spread - Shah, Damber Bikram; Karki, Prasanna; Poudel, Prakash; Joshi, Sumit; Upadhhya, Prabhaw; Sharma, Gopal Raman (Nepal Journal of Neuroscience, 2020)
Lymphoplasmacyte-rich meningioma is a rare variant of World Health Organization (WHO) Grade I meningioma, which may present as diffuse granulomatous disease with leptomeningeal spread. Here, we report a case of 61 years old man who presented with gradual onset of progressive quadriperesis. Patient was initially treated with antitubercular medications as imaging studies and serum markers were suggestive of granulomatous lesion. Surgical intervention was adviced as patient did not respond to medical management. Histopathology and immunohistochemistry confirmed the diagnosis of lymphoplasmacyte-rich meningioma. This meningioma can present as diffuse leptomeningeal infiltrative lesion involving both the hemispheres and all the tentorial surfaces mimicking inflammatory lesion. Tuberculosis is very common in our part and the diffuse infiltrative nature oflymphoplasmacyte-rich meningioma with similar radiological features of these two pathologies may confuse and delay the diagnosis. Recognition of this entity is of utmost importance as it guides proper management.